A straightforward protocol for Hf purification by single step anion-exchange chromatography and isotopic analysis by MC-ICP-MS applied to geological reference materials and zircon standards - Yang, Y.; Wu, F.; Wilde, Simon; Xie, L. (Elsevier Science BV, 2011)
A straightforward one-step Hf purification protocol for geological samples using common anionexchangechromatography and isotopic measurements by multiple collector inductively coupled plasma mass spectrometry (MC-ICP-MS) is described in this paper. The sample is dissolved in concentrated HF–HNO3 mixtures with round-bottom SavillexTM Teflon screw-top capsules or high-pressure stainlesssteel jacketed Teflon bombs. After complete dissolution, the chemical separation between Hf and isobarically interfering elements such as Lu, Yb, and matrix elements like Ti, is performed and achievedsimultaneously using a common one-step anion exchange resin (AG1-X8). The Hf yields are >90% andtotal procedural blanks are lower than 20 pg. This protocol not only avoids using multiple-stage ionexchange resins, but also eliminates perchloric acid to break down fluorides after HF treatment of thesample. In addition to whole rock, this protocol is also practical for zircon and baddeleyite Hf purificationprior to isotopic measurement. New Hf isotopic data for zircon 91500, Temora, CN92-1 and FM0411,together with Phalaborwa baddeleyite are presented for this method. Multiple analyses of the international geological reference materials and standard zircon and baddeleyite used in U–Pb geochronology demonstrate that this method is simple, economic, efficient and reproducible.